Kohesi dan Koherensi Paragraf pada Teks Berita Tribun News dalam Jaringan (Daring) - ., Aisah; Putrayasa, I G.N.K. (Humanis; Vol 20 No 1 (2017), 2017)
This research entitled “cohesion and coherence Tribun’s news text in network”. Cohesion lexical stuffs, cohesion grammatical stuffs, and the connection in Tribun news text May-July editions will be the problems of studied. Basd on that problem of study, this research aim to describe cohesion and grammatical lexical toolsof the news text, also explain the connection of meaning or coherence in Tribun’s news text May-July 2016 editions. The approach that used in this research is descriptive qualitative, and the data source is text news of Tribun News May-July 2016 edition. This research used random system , so not all the news that published on May-July 2016 will be analyzed. The data that will be analyzed consists of nine news text. The technique that used in collecting data are listenand note. The data analysis in this research used agih method with the base technique for the exact element. Method of presenting the results of the analysis using formal and informal methods. Based on the research, it was proove some: (1) the use grammatical cohesion including reference, substitution, elipsis, and conjuction; (2) the use lexical cohesion including synonim, antonym, repetition, collocation, and equivalence; (3) the use of coherency or meaning relation including cause and effect, means of result, background conclusion, alllowance result, terms result, and comparations connection. In conclusion, the most cohesiveness that appeared the best is, grammatical reference cohesion, while cause and effect is the meaning connection that dominate in the Tribun’s text news May-July 2016 editions.